AlgoRhythm - A Sorting and Path-finding visualizer tool to improve existing algorithms teaching methodologies - Trivedi, Arpit; Pandey, Kartikey; Gupta, Vaibhav; Jha, Mukesh Kumar (2023 13th International Conference on Cloud Computing, Data Science & Engineering (Confluence), 2023)
Visualization of algorithms has helped bring a breakthrough in computer science education but it is yet to make its way to schools/colleges' lecture halls as the main educational tool. It is not a hidden fact that the process of teaching and learning algorithms is often complex and the difficulty level increases with every next algorithm in the list. An algorithm visualizer can be a useful tool to help students understand and learn such algorithms. Our work is exactly the tool that helps its users to grasp the knowledge behind these algorithms in a fun, interactive, and self-paced environment. This paper outlines the architecture of the resulting tool, AlgoRhythm. The tool currently focuses on different sorting and path-finding algorithms and visualizing them on a canvas where users can play around, interact, and modify both code and data to learn and improve their understanding of the same. Also, with the added support of an in-built IDE, our work transcends the existing algorithm teaching methodologies. It is intended to be used as a supplement tool for teaching or as a stand-alone application for algorithm visualization. A study with AlgoRhythm is described, showing that there is an advantage of using this tool over traditional methods and the interest in learning displayed by students using this tool is significantly higher.